RFID technology and applications - Miles, Stephen B. 1954-; Sarma, Sanjay E. 1948-; Williams, John R. 1968- (Cambridge University Press, 2008)
Are you an engineer or manager working on the development and implementation of RFID technology? If so, this book is for you. Covering both passive and active RFID systems, the challenges to RFID implementation are addressed using specific industry research examples and common integration issues. Key topics include RF tag performance optimization, evaluation methodologies for RFID and Real-Time-Location Systems (RTLS) and sensors, EPC network simulation, RFID in the retail supply chain, and applications in product lifecycle management, anti-counterfeiting and cold chain management.